Expression Patterns of Circular RNAs in High Quality and Poor Quality Human Spermatozoa - Chioccarelli, Teresa; Manfrevola, Francesco; Ferraro, Bruno; Sellitto, Carolina; Cobellis, Gilda; Migliaccio, Marina; Fasano, Silvia; Pierantoni, Riccardo; Chianese, Rosanna (Frontiers in Endocrinology, 2019)
Circular RNAs (circRNAs) are expressed in human testis and seminal plasma. Until today, there is missing information about a possible payload of circRNAs in human spermatozoa (SPZ). With this in mind, we carried out a circRNA microarray identifying a total of 10.726 transcripts, 28% novel based and 84.6% with exonic structure; their potential contribution in molecular pathways was evaluated by KEGG analysis. Whether circRNAs may be related to SPZ quality was speculated evaluating two different populations of SPZ (A SPZ= good quality, B SPZ= low quality), separated on the basis of morphology and motility parameters, by Percoll gradient. Thus, 148 differentially expressed (DE)-circRNAs were identified and the expression of selected specific SPZ-derived circRNAs was evaluated in SPZ head/tail-enriched preparations, to check the preservation of these molecules during SPZ maturation and their transfer into oocyte during fertilization. Lastly, circRNA/miRNA/mRNA network was built by bioinformatics approach.